PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN PERTAMBANGAN DI INDONESIA - Rina Masithoh Haryadi, Helmin Nurdiansyah Titin Ruliana 2 (EKONOMIA, 2021)
The formulation of the problem in this research is whether disclosure of Corporate Social Responsibility has a significant effect on the financial performance of mining sector companies in Indonesia. The purpose of this study was to determine the effect of corporate social responsibility disclosure on the financial performance of mining sector companies in Indonesia. The hypothesis of this study is the influence of Corporate Social Responsibility on the financial performance of mining sector companies in Indonesia. The data needed in this study is secondary data obtained from the ratio data of financial statements and sustainable reports of mining companies in 2016-2018 obtained from each company's website. The results of data processing obtained tcount = 0.704 where the value is smaller than the value of ttable = 2.073 and the significance value of 0.489 is greater than the probability value of 0.05, which means the Corporate Social Responsibility variable does not have a significant effect on financial performance. Based on the conclusions in this study, the hypothesis which states that Corporate Social Responsibility has a significant effect on financial performance is rejected.